Empowering women dairy farmers through scientific dairy farming practices - KUMAR, SANJEEV; RANJAN, SANJEEV; KUMAR, SURYAMANI; KUMAR, SANJAY (The Indian Journal of Animal Sciences, 2018)
The study was carried out in 6 villages of operational area of KVK, Nalanda, about the knowledge levels of the women dairy farmers with respect to the different component of Scientific Dairy Farming Practices (SDFP). Fifteen farmers from each village constituting the sample size of 90 farmers were included in the survey. The responses of the farmers were collected and statistically analyzed. The study revealed that majority of farmers had medium knowledge on different components of SDFP. But, very few farmers had high knowledge about the SDFP, which showed that different dairy development agencies working in Nalanda district were not providing adequate knowledge to the farmers. The knowledge index of different aspect of SDFP, viz. breeding, feeding, health care and management were 42, 37.84, 39.75 and 41.73%, respectively, and overall knowledge index of SDFP was 39.63, which indicated poor knowledge level of farmers in the study area. Therefore, the KVK, Nalanda should make proper action plan in which more training programmes could be organized on SDFP especially for women dairy farmers to empower them in dairying.